Seasonality period of production in irrigated pastures - Rassini, Joaquim Bartolomeu (Pesquisa Agropecuaria Brasileira, 2004)
This study was conducted to evaluate the seasonal period of dry matter production of irrigated forages species: Elephantgrass (Pennisetum purpureum), Guineagrass cv. Tanzania (Panicum maximum), Signalgrass (Brachiaria decumbens), Tannergrass (Brachiaria bryzantha), Pojucagrass (Paspalum atratum) and Bermudagrass cv. Coastcross (Cynodon dactylon). Climatic conditions and forages cycles were evaluated during two years (1999/2000 and 2000/2001). The seasonal production of irrigated pastures is of 65 to 70 days in the year. In such seasonal period there is no dry matter production even when hydric requirements of grasses are met through irrigation.